2021
DOI: 10.3389/fphar.2020.586993
|View full text |Cite
|
Sign up to set email alerts
|

Potential Natural Products Against Respiratory Viruses: A Perspective to Develop Anti-COVID-19 Medicines

Abstract: The emergence of viral pneumonia caused by a novel coronavirus (CoV), known as the 2019 novel coronavirus (2019-nCoV), resulted in a contagious acute respiratory infectious disease in December 2019 in Wuhan, Hubei Province, China. Its alarmingly quick transmission to many countries across the world and a considerable percentage of morbidity and mortality made the World Health Organization recognize it as a pandemic on March 11, 2020. The perceived risk of infection has led many research groups to study COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 110 publications
0
49
0
Order By: Relevance
“…For most viral infections, treatment consists of synthetic drugs, including agents such as neuraminidase inhibitors (zanamivir and oseltamivir), channel blockers (amantadine and rimantadine), viral polymerase inhibitors (favipiravir and baloxavir-marboxi), ribavirin, lopinavir-ritonavir, interferon, corticosteroids, and many others ( Omrani et al, 2021 ). Their low efficacy and the development of viral resistance led to an increasing interest in natural products as an important source of antiviral and inhibitory activities.…”
Section: Natural Products With Antiviral Activitymentioning
confidence: 99%
“…For most viral infections, treatment consists of synthetic drugs, including agents such as neuraminidase inhibitors (zanamivir and oseltamivir), channel blockers (amantadine and rimantadine), viral polymerase inhibitors (favipiravir and baloxavir-marboxi), ribavirin, lopinavir-ritonavir, interferon, corticosteroids, and many others ( Omrani et al, 2021 ). Their low efficacy and the development of viral resistance led to an increasing interest in natural products as an important source of antiviral and inhibitory activities.…”
Section: Natural Products With Antiviral Activitymentioning
confidence: 99%
“…In the research in this area, it has been observed that flavonoids, a class of natural polyphenolic compounds commonly found in plants, have a striking potential against the virus. It has been stated that this phytochemical, which has various pharmacological properties, especially antioxidant, antiviral, anti-inflammatory, and antineoplastic activities, exhibits inhibitory properties in almost every step in the viral cycle of SARS-CoV-2 [321]. Baicalin (EC 50 : 12.5 µg/mL), a bioactive glycosylated flavonoid found especially in Citrus species, while showing the most effective antiviral activity as an ACE2 inhibitor against the prototype SARS virus growing in the fetal Rhesus Kidney-4 (FRhK-4) cell line [322,323], an in silico study made for TMPRSS2 of SARS-CoV-2 has also shown that it acted as a natural inhibitor.…”
Section: Potential Natural Products Against Covid-19mentioning
confidence: 99%
“…Furthermore, in an in vitro study, it was specified that contents of capsules in traditional Chinese medicine (Lianhua Qingwen) showed antiviral and anti-inflammatory activity by inhibiting SARS-CoV-2 replication. Again, when the same capsules are combined with Ribavirin, Lopinavir/Ritonavir, and Umifenovir basic therapy, and administered to patients infected with SARS-CoV-2, it has been reported that many important symptoms are overcome in a remarkably short time [321]. When we look at the evidence we have, there are many promising but disorganized and unsubstantiated studies on natural products.…”
Section: Potential Natural Products Against Covid-19mentioning
confidence: 99%
“…Instead of synthetic compound being developed, natural products should be one alternative to speed up the discovery of SARS-CoV-2 antiviral agent [20] . Unfortunately, to the best of our knowledge, there has been less studies reporting compounds from natural products having in vitro / in vivo activity against the virus.…”
Section: Introductionmentioning
confidence: 99%